Efectividad diagnóstica del método clínico Johnson-Toshach y el ponderado fetal por ecografía en el diagnóstico de macrosomía fetal en gestantes a término Hospital Carlos Monge Medrano de Juliaca 2023 - Cruz Molina, Hugo Godofredo (2024)
The objective of the study is "to analyze the diagnostic effectiveness of the Johnson-Toshach method compared to fetal weight estimation by ultrasound for evaluating fetal macrosomia in term pregnant women attended at the Carlos Monge Medrano Hospital in Juliaca in 2023." This study is observational, analytical, longitudinal, and retrospective, with a cross-sectional design. A sample of medical records of patients diagnosed with fetal macrosomia at the Carlos Monge Medrano Hospital in Juliaca will be used. Data will be collected using a structured form designed according to the study's objectives to capture relevant variables. The analysis will be conducted using SPSS software version 25. The results are expected to demonstrate a high diagnostic accuracy of the Johnson-Toshach method, with a prevalence above the national average. Furthermore, it is anticipated that the sensitivity, specificity, and positive and negative predictive values of the method will exceed 80%.